IMPLEMENTATION OF MULTICULTURAL VALUES IN DEVELOPING STUDENTS SOCIAL INTELLIGENCE (PHENOMENOLOGICAL STUDIES IN SOCIAL STUDIES LESSONS AT SMKN 1 CIHAMPELAS) - Fajar, Arnie; Hendrawan, Jajang Hendar; Widaningsih, Iis (International Conference On Social Science Education, 2023)
This study aims to describe the process and results of implementing multicultural values in developing the social intelligence of students in social studies subjects at SMKN 1 Cihampelas, West Java Province. The research approach used is qualitative descriptive with a study of phenomenological studies. The instruments used are observation, interviews, and documentation. Data analysis begins with describing all phenomena experienced by research subjects, horizonalization, cluster of meaning, description of essence, and report of research results. The study results: 1) Social studies teachers plan to learn through syllabi and lesson implementation plans referring to Permendikbudristek No. 16 of 2022; 2) Social studies teachers carry out learning, including introduction, core, and closing activities. Implementing multicultural values has implications for the development of social intelligence; students show empathy, can carry themselves, cooperate, express themselves, and communicate by expressing opinions, ideas, and arguments, as well as mutual need/interdependence; 3) The teacher conducts an assessment covering three aspects, attitudes, knowledge, and skills, which are carried out at the end of the learning process. 4) The supporting factors are the teacher carrying out the learning process following the lesson implementation plan, the support of all school residents, and the positive response from students. The inhibiting factors are inadequate learning facilities, social studies teachers not having a physical form of the systematic assessment form, and lack of supervision from the principal related to learning administration.